In vitro Shoot Proliferation and Plant Regeneration of Phlogacanthus thyrsiflorus Nees. a Rare Medicinal Shrub of Bangladesh - Hassan, A.K. M. Sayeed; Begum, Nadira; Sultana, Rebeka; Khatun, Rahima (Plant Tissue Culture and Biotechnology, 2011)
An efficient protocol was developed for shoot proliferation and plant regeneration of Phlogacanthus thyrsiflorus Nees. (Acanthaceae) - a rare medicinal shrub of Bangladesh, through in vitro culture using shoot tip and nodal explants. Best shoot induction was observed on MS with 1.0 mg/l BAP + 0.5 mg/l NAA, in which 84.2% of nodal explants responded to produce maximum number (12.4 ± 0.66) of shoots per culture. In vitro raised shoots rooted on half-strength MS with 0.5 mg/l IBA + 0.5 mg/l NAA. For acclimation and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 85%. Key words: Phlogacanthus thyrsiflorus, Shoot proliferation, Plant regeneration D. O. I. 10.3329/ptcb.v21i2.10236 Plant Tissue Cult. & Biotech. 21(2): 135-141, 2011 (December)